Factors that influence the academic performance of students majoring in Licenciatura en Idioma Inglés: opción Enseñanza and in Licenciatura en Lenguas Modernas especialidad en Frances e Ingles in the main campus of the University of El Salvador - González Zavaleta, Daniel Esaú; Cabrera Alvarenga, Karina Elizabeth; Palacios, José Manuel; Oliva, José Israel; Garay Salinas, Ricardo (San Salvador : Universidad de El Salvador, 2013)
The principal aim of this study is to describe the factors that influence the academic performance of third-year students majoring in Licenciatura en Idioma Inglés Opción Enseñanza and also in Licenciatura en LenguasModernas Especialidad en Frances e Ingles in Semester II-2012. Researchers planned to carry out this project because they realized that there are students who work and study at the same time, have family responsibilities and do not have any background of the two languages involved. So, this study intends to find out if these students’ personal profiles might lead them either to academic success or to failure. This study aimsat understanding the relationship between academic performance and personal and academic factors of students studying the two target majors. Researchers used a Semi-structured Interview so that the participants could provide both personal and academic information that relate to their academic performance.
Anexos.
Tesis -- (Licenciatura en Idioma Inglés, opción Enseñanza) -- Universidad de El Salvador, San Salvador, 2013
Bibliografía : hojas 36-38
Audiencia general
Keywords: Inglés -- Enseñanza; Adquisición de segundo lenguaje; Rendimiento académico